2008
DOI: 10.1177/0960327108098332
|View full text |Cite
|
Sign up to set email alerts
|

Serum and BAL cytokine and antioxidant enzyme levels at different stages of pneumoconiosis in coal workers

Abstract: Coal workers’ pneumoconiosis (CWP) is an occupational pulmonary disease that occurs by chronic inhalation of coal dust. CWP is divided into two stages depending on the extent of the disease, as simple pneumoconiosis (SP) and progressive massive fibrosis (PMF). In the present study, serum and bronchoalveolar lavage (BAL) cytokine (interleukin-1β [IL-1β], IL-6, tumor necrosis factor-α [TNF-α], transforming growth factor-β [TGF-β]) and antioxidant enzymes levels, their relation with the disease severity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
(46 reference statements)
2
13
0
Order By: Relevance
“…Preliminary populations findings showed that IL6 mRNA expression in peripheral blood of patients with pneumoconiosis was significantly higher than in that of controls, and in line with the screening results (3.271 times) and reports 23 , 24) . IRF2 and PTGS2 results were inconsistent with the screening results (3.269 times and 3.361 times, respectively).…”
Section: Discussionsupporting
confidence: 86%
“…Preliminary populations findings showed that IL6 mRNA expression in peripheral blood of patients with pneumoconiosis was significantly higher than in that of controls, and in line with the screening results (3.271 times) and reports 23 , 24) . IRF2 and PTGS2 results were inconsistent with the screening results (3.269 times and 3.361 times, respectively).…”
Section: Discussionsupporting
confidence: 86%
“…13,28 In particular, THP-1 cells have been proven helpful to study the pro-inflammatory and pro-fibrotic effects of LAR nanomaterials such as multiwalled carbon nanotubes (MWCNTs). 21,29 Using confocal microscopy to study uptake of fluorescein isothiocyanate (FITC)-labeled La 2 O 3 and Gd 2 O 3 nanoparticles, we found that most of the labeled nanoparticles colocalized with an Alexa fluor 594-labeled LAMP1-positive compartment with coefficients of colocalization ranging from 66 to 91% by Image J analysis (Figure 2A and S2A).…”
Section: Resultsmentioning
confidence: 99%
“…4,8 IL-6 is a cytokine that has been associated with silicosis. The study by Ulker et al 23 showed that bronchoalveolar lavage and the plasma concentrations of IL-6, IL-1b, and TNF-a were elevated in patients with pneumoconiosis, with higher levels found in patients with progressive massive fibrosis. Sauni et al 4 found elevated IL-6 plasma levels in construction workers exposed to silica.…”
Section: Discussionmentioning
confidence: 99%